Varroa destructor economic injury levels and pathogens associated with colony losses in Western Canada - Morfin, Nuria; Foster, Leonard J.; Guzman-Novoa, Ernesto; Van Westendorp, Paul; Currie, Robert W.; Higo, Heather (Frontiers in Bee Science, 2024)
Introduction The honey bee parasitic mite, Varroa destructor, is considered the main factor associated with winter colony losses. To control this mite, beekeepers must implement Integrated Pest Management (IPM) strategies. An effective IPM strategy is based on timely monitoring of mite levels to treat the colonies when the mites reach an economic threshold and before they grow to damaging levels (economic injury level). Additionally, concerns have been raised about the possible interaction between V. destructor and other stressors; stressors acting additively or synergistically may lead to high colony mortality. Methodology Varroa destructor levels were recorded in colonies from five regions of British Columbia, Canada: Lower Mainland, Kootenay, Okanagan, Cariboo, and Peace. Mite levels were analyzed for associations with colony strength and mortality, as well as with other pathogens that were identified using total RNA sequencing. Results The Kootenay and Lower Mainland regions had the highest V. destructor levels in the fall (3.38±0.65 and 2.51±0.57, respectively) followed by the Okanagan (1.54±0.36), Cariboo (1.31±0.39), and Peace (0.66±0.25) regions. The Peace region had a significantly lower proportion of dead colonies than the other regions. Varroa destructor levels in the fall significantly predicted odds of colony mortality in the spring. Colonies with ≥ 1% mite infestation in the fall (August) had a significantly higher mortality rate (p=0.005) compared to colonies with <1% mite levels. Therefore, treatment is recommended above that threshold. Also, deformed wing virus-B levels were 8.4 times higher than those of deformed wing virus-A variant in all the regions and were highest in the Kootenay region, which also had the highest rate of colony losses. Lastly, Malpighamoeba mellificae and Nosema (Vairimorpha) apis transcripts were identified along with other pathogens that deserve further investigation, including Apis mellifera filamentous virus, Apis rhabdovirus, Lake Sinai virus, Varroa tymo-like, and Apis mellifera solinvivirus 1. Discussion The dynamic nature of host-pathogen interactions requires frequent pathogen surveillance to determine the prevalence and levels of parasitic mites and associated infectious diseases, and their impact on honey bee health, not only in the regions of this study, but globally. Nevertheless, more studies are needed to determine the nature of the type of interaction between the identified pathogens and V. destructor. Also, more research is needed to evaluate their potential impact on colony survival, to provide accurate mite and disease control recommendations to beekeepers.